Wifi Fingerprinting Based Position Determination - Prasetya, F.X. Hendra; Aji Nugroho, Robertus Setiawan (PROXIES, 2013)
Paper in this research aims to determine the position of a point by using fingerprinting techniques. Locations used in this research is building Henrlcus Constant Unika Soegijapranata Semarang. Building 8th Floor Henricus Constant mainly have some point the Access Point (AP), based on APs signal strength wiU be measured at specific points. Results of these measurements as a reference for determining the location / points. Keyword: FIngerprinting, wiJi, position determination